1988
DOI: 10.1002/j.1460-2075.1988.tb02904.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic stimulation of thymocytes results in the calcium-dependent phosphorylation of c-ets-1 proteins.

Abstract: Human, murine and chicken c‐ets‐1 proteins migrate in SDS‐polyacrylamide gels as multiple species. We show here that most if not all of this heterogeneity is due to phosphorylation events occurring predominantly on serine and to a lesser extent on threonine residues. These phosphorylations can be specifically and rapidly stimulated by treatment with the calcium ionophore A23187 or abolished by lowering the extracellular calcium concentration to less than 0.1 microM. The products encoded by c‐ets‐2 are also pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 38 publications
1
74
0
1
Order By: Relevance
“…These observations suggest integration between di erent T cell signaling pathways, mediated by the formation of Stat5 and Ets-1/2 protein complex in solution that can then form higher order oligomeric complexes on DNA. IL-2 activates Stat5 via activation of protein tyrosine kinases Jak1 and Jak3 associated with receptor components (Ihle et al, 1997;Lin and Leonard, 1997) whereas T cell activation results in calcium-dependent serine phosphorylation and activation of Ets-1/2 proteins (Bassuk and Leiden, 1997;Pognonec et al, 1988). Several studies have placed Ets-1 and Ets-2 in the Ras/MAPK signaling pathway (Co er et al, 1994;Miyazaki and Taniguchi, 1996;Rabault et al, 1996;Yang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest integration between di erent T cell signaling pathways, mediated by the formation of Stat5 and Ets-1/2 protein complex in solution that can then form higher order oligomeric complexes on DNA. IL-2 activates Stat5 via activation of protein tyrosine kinases Jak1 and Jak3 associated with receptor components (Ihle et al, 1997;Lin and Leonard, 1997) whereas T cell activation results in calcium-dependent serine phosphorylation and activation of Ets-1/2 proteins (Bassuk and Leiden, 1997;Pognonec et al, 1988). Several studies have placed Ets-1 and Ets-2 in the Ras/MAPK signaling pathway (Co er et al, 1994;Miyazaki and Taniguchi, 1996;Rabault et al, 1996;Yang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For competition experiments, unlabeled double-stranded oligonucleotides were pre-incubated with cell extracts for 10 min at RT prior to addition of the probe. Immunoassays were performed by incubating the binding reactions 30 min at 48C with antisera directed against Ets1/2 (#8), Fli-1 (#61), Tel (#69), Ets-1 (#49), Ets-2 (#36) (Bailly et al, 1994;Pognonec et al, 1988), GABPa, GABPb (de la Brousse et al, 1994), Stat3, Stat4, Stat6 (Transduction Laboratories), Elf-1, Sp1, Stat5a, Stat5b, Stat5 C17 which recognizes both Stat5a and Stat5b (Santa Cruz Biotechnology), as indicated in Figure legends. DNA binding proteins were isolated from whole cell extracts as described (Beadling et al, 1994).…”
Section: Cell Culturementioning
confidence: 99%
“…It disappeared when PKCa expression was fully re-established (lane 5). A decrease in the mobility of the Ets1 protein can be caused by phosphorylation (Pognonec et al, 1988;Ballschmieter et al, 2003). We, therefore, incubated SK-Mel protein extracts containing the slower migrating Ets1 form with alkaline phosphatase.…”
Section: Suppression Of Endogenous Pkca Expression Results In Downregmentioning
confidence: 99%
“…Ets1 is an effector of PKCa M Vetter et al Phosphorylation can have positive or negative effects on the activity of the Ets1 protein, depending on where phosphorylation on the Ets1 protein has taken place (Pognonec et al, 1988;Yang et al, 1996;Cowley and Graves, 2000;Seidel and Graves, 2002). Phosphorylation at the N-terminus by ERK1/2 leads to Ets1 superactivation (Yang et al, 1996;Seidel and Graves, 2002), whereas phosphorylation of the exon-VII domain by calcium or CaMKII results in inhibition of the Ets1 DNA-binding activity (Pognonec et al, 1988;Cowley and Graves, 2000). In previous studies, PKCa has been shown to interfere with the activities of ERK1/2 as well as with that of CaMKII.…”
Section: Sipa Interferes With Ets1 Protein Synthesis and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation